Lactococcus lactis secreting phage lysins as a potential antimicrobial against multi-drug resistant Staphylococcus aureus - Chandran, Carumathy; Tham, Hong Yun; Abdul Rahim, Raha; Lim, Swee Hua Erin; Yusoff, Khatijah; Song, Adelene Ai Lian (PeerJ, 2022)
Background. Staphylococcus aureus is an opportunistic Gram-positive bacterium that can form biofilm and become resistant to many types of antibiotics. The treatment of multi-drug resistant Staphylococcus aureus (MDRSA) infection is difficult since it possesses multiple antibiotic-resistant mechanisms. Endolysin and virion-associated peptidoglycan hydrolases (VAPGH) enzymes from bacteriophage have been identified as potential alternative antimicrobial agents. This study aimed to assess the ability of Lactococcus lactis NZ9000 secreting endolysin and VAPGH from S. aureus bacteriophage 88 to inhibit the growth of S. aureus PS 88, a MDRSA. Method. Endolysin and VAPGH genes were cloned and expressed in L. lactis NZ9000 after fusion with the SPK1 signal peptide for secretion. The recombinant proteins were expressed and purified, then analyzed for antimicrobial activity using plate assay and turbidity reduction assay. In addition, the spent media of the recombinant lactococcal culture was analyzed for its ability to inhibit the growth of the S. aureus PS 88. Results. Extracellular recombinant endolysin (Endo88) and VAPGH (VAH88) was successfully expressed and secreted from L. lactis which was able to inhibit S. aureus PS 88, as shown by halozone formation on plate assays as well as inhibition of growth in the turbidity reduction assay. Moreover, it was observed that the spent media from L. lactis NZ9000 expressing Endo88 and VAH88 reduced the viability of PS 88 by up to 3.5-log reduction with Endo88 being more efficacious than VAH88. In addition, Endo88 was able to lyse all MRSA strains tested and Staphylococcus epidermidis but not the other bacteria while VAH88 could only lyse S. aureus PS 88. Conclusion. Recombinant L. lactisNZ9000 expressing phage 88 endolysin may be potentially developed into a new antimicrobial agent for the treatment of MDRSA infection.